An analysis of efficiency and loan loss provisioning behaviour in Japanese banking - Wu, J.Y. (2017)
The dissertation aims to investigate the loan loss provision behaviours in Japanese banks over the sample period 2010 to 2016 with respect to cost efficiency and three hypotheses (earning management, capital management and business cycle) based on relevant empirical literatures and 64 Japanese banks. There are two main models employed in the dissertation. First of all, cost efficiency will be assessed via the Stochastic Frontier Approach (SFA) model which explored that overall efficiency score for Japanese banks in each year is nearly over 80% and indicated Japanese banks maintained financial stability efficiently. In addition, Generalized Method of Moments (GMM) model is adopted to analyse loan loss provision behaviours. As a consequence, some available results support cost efficiency in Japanese banks, while there is no clear evidence to support earning management, capital management and business cycle.